A reabilitação do preso: exigência da democracia - Gomes, Karin Pfannemüller (2011)
The democratic framework is based on freedom, equality and plurality ideas, which are fundamental rights inherent to individuals. Those rights' warranties are mandatory to State and shared by citizens. The diverse freedom and equality visions converge to human dignity concept, which is inherent to the unique living species that have the capability of loving and think: human kind. The acknowledgement of differences, plurality and mutual respect belong to human kind itself, in the democratic framework. In this context, democracy has been in a transformation process, according to society's needs and expectations, and taking into account new citizenship concepts. Infractions, crimes and penalties have been spreading throughout society since the origins of humanity. Its purposes and application have been continuously changing as well. Among infinite doctrines and existing theories, an infraction‟s possibility of rehabilitation and re-insertion in society is brought to attention, along with his return to labor market, society and even so, active citizenship. Penalty crisis, state repression and society's discredit on prison system confirm the ideal of penalty's abolition, condemned's possibility of regeneration and prison's collapse theories. Meanwhile, democracy demands the application of particular conditions that act as a criminal's regeneration catalyst. Thus, the objective of this research is identifying legal and actual conditions in Brazil that promote criminal's rehabilitation and reintegration in society. Those conditions are demanded by the democratic regime and based on fundamental rights principles.